2012
DOI: 10.1093/jxb/ers142
|View full text |Cite
|
Sign up to set email alerts
|

Variation in vein density and mesophyll cell architecture in a rice deletion mutant population

Abstract: There is a need to develop rice plants with improved photosynthetic capacity and efficiency in order to enhance potential grain yield. Alterations in internal leaf morphology may be needed to underpin some of these improvements. One target is the production of a ‘Kranz-like’ anatomy, commonly considered to be required to achieve the desired levels of photosynthesis seen in C4 crops. Kranz anatomy typically has two or three mesophyll cells interspersing adjacent veins. As a first step to determining the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…It has been reported earlier that an increase in vein number per unit area in rice leaves was due to a change in vein diameter or due to the reduced size of other cells as an immediate compensatory mechanism [20, 61]. Here we demonstrate that the increase in vein number in Oryza can also be due to an actual change in the number of mesophyll cells rather than just having a change in cell size (S4 Table).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It has been reported earlier that an increase in vein number per unit area in rice leaves was due to a change in vein diameter or due to the reduced size of other cells as an immediate compensatory mechanism [20, 61]. Here we demonstrate that the increase in vein number in Oryza can also be due to an actual change in the number of mesophyll cells rather than just having a change in cell size (S4 Table).…”
Section: Discussionsupporting
confidence: 67%
“…There have been some studies to understand the function of bulliform cells [1719], and more recently the variation in vein patterning and mesophyll architecture in a mutant population of IR64 [20]. Of late, there has been growing interest in the characterization of the foliar structure of wild rice ancestors [21, 22], which include some of the wild species used in this structure-function study.…”
Section: Introductionmentioning
confidence: 99%
“…The functional allele of ERECTA reduced stomatal density and thereby lowered stomatal conductance relative to loss-of-function alleles; for this reason, ERECTA is regarded as a transpiration efficiency gene. Recently, rice mutants generated by artificial mutagens were screened for mesophyll cell architecture with the goal of improving photosynthetic capacity47. Several mutant lines showed favourable alterations such as increased mesophyll cell size.…”
Section: Discussionmentioning
confidence: 99%
“…Mesophyll cells are more numerous in C 3 than C 4 plants, which increases IVD in C 3 plants7072 and reduces their K leaf 2343. Smillie et al 73 reported that IVD of rice plants is more dependent on cell size than cell number, which suggests that the lower IVD under water deficit conditions is mostly a result of more tightly packed, small mesophyll cells. The tightly packed mesophyll cells in smaller leaves under water deficit (Table 2) would produce more resistance in the apoplastic pathway for water transport in leaves, which would decrease K leaf and the subsequent K plant .…”
Section: Discussionmentioning
confidence: 99%
“…Rice leaf veins were divided into three categories based on their size (i.e., midrib, major and minor veins) to calculate the leaf vein density73. One centimeter leaf sections were excised with a razor blade from the middle portion of newly-developed leaves after measuring the leaf width.…”
Section: Methodsmentioning
confidence: 99%